CVD precursors for transition metal oxide nanostructures: molecular properties, surface behavior and temperature effects (Phys. Status Solidi A 2∕2014). Issue 2 (February 2014) - Tabacchi, Gloria; Fois, Ettore; Barreca, Davide; Gasparotto, Alberto
<x xml:space="preserve">Abstract</x> The molecular origin of the behavior of a class of transition metal complexes, attractive as sources for the chemical vapor deposition (CVD) growth of metal/metal oxide nanomaterials, is unraveled by integrated modeling studies. In the paper on pp. 251–259, Tabacchi et al. show how the metal center affects the properties of a series of β‐diketonate‐diamine metal complexes (M = Fe, Co, Cu, Zn), by focusing on the growth‐temperature influence on the first molecular activation stages. A key milestone of the present work is the observation of hot‐surface induced molecular rolling for Zn(hfa)2TMEDA, the complex with the most symmetric coordination polyhedron in the gas phase. Such a rolling motion occurs at temperatures even lower than those normally adopted in CVD processes and causes rearrangement of the ligands around the metal center. Variations in the behavior of different metal complexes might be at the origin of different decomposition pathways at the growth surface, enabling thus to shed light on the molecule‐to‐material conversion processes and to tailor the initial nucleation stages of the target nanomaterials by design. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>